Tropical rainfall over the last two millennia: evidence for a low-latitude hydrologic seesaw - Lechleitner, Franziska A.; Breitenbach, Sebastian Franz Martin; Rehfeld, Kira; Ridley, Harriet E.; Asmerom, Yemane; Prufer, Keith M.; Marwan, Norbert (Dr.); Goswami, Bedartha; Kennett, Douglas J.; Aquino, Valorie V.; Polyak, Victor; Haug, Gerald H.; et al. (Scientific Reports, 2017)
The presence of a low-to mid-latitude interhemispheric hydrologic seesaw is apparent over orbital and glacial-interglacial timescales, but its existence over the most recent past remains unclear. Here we investigate, based on climate proxy reconstructions from both hemispheres, the inter-hemispherical phasing of the Intertropical Convergence Zone (ITCZ) and the low-to mid-latitude teleconnections in the Northern Hemisphere over the past 2000 years. A clear feature is a persistent southward shift of the ITCZ during the Little Ice Age until the beginning of the 19th Century. Strong covariation between our new composite ITCZ-stack and North Atlantic Oscillation (NAO) records reveals a tight coupling between these two synoptic weather and climate phenomena over decadal-to-centennial timescales. This relationship becomes most apparent when comparing two precisely dated, high-resolution paleorainfall records from Belize and Scotland, indicating that the low-to mid-latitude teleconnection was also active over annual-decadal timescales. It is likely a combination of external forcing, i.e., solar and volcanic, and internal feedbacks, that drives the synchronous ITCZ and NAO shifts via energy flux perturbations in the tropics.